Effects of Enhanced Phytoremediation Techniques on Soil Aggregate Structure - Qiao Yang; Hao Yu; Zhongqiu Zhao; Zhengshan Ju (Agriculture)
In response to the current serious problem of soil cadmium (Cd) contamination in agricultural land, phytoremediation technology is a green and environmentally friendly application prospect; however, its remediation efficiency is currently limited. An enhanced phytoremediation technique was constructed using the biodegradable chelator aspartate diethoxysuccinic acid (AES) combined with the plant growth regulator gibberellic acid (GA3) to enhance the formation of maize. This technique has been proven to have a superior remediation effect. However, the safety of the restoration technique is of particular importance. The remediation process not only removes the contaminants, but also ensures that the original structure and stability of the soil is not damaged. In this regard, the constructed enhanced phytoremediation technique was further investigated in this study using soil columns. In combination with microscopic tests, such as X-ray diffraction and scanning electron microscopy, this study investigated the effects of the remediation process on the distribution characteristics of Cd in soil aggregates, and the structure and stability of soil aggregates. This was conducted by analyzing, as follows: plant growth conditions; the morphology, structure and mineral composition of soil aggregates in different soil layers; and the changes in these characteristics. The results demonstrated that the enhanced phytoremediation technique constructed in this study has a negligible impact on the morphology and mineral composition of soil aggregates, while exerting a limited influence on soil structure stability. This indicates that the technique can facilitate the safe utilization of remediated contaminated soil.